RADIONUCLIDE DIAGNOSTICS TO STUDY OF HEPATOBILIARY SYSTEM AFTER SURGICAL REMOVAL OF THE GALLBLADDER. POSTCHOLECYSTECTOMICAL SYNDROME - Y. Adamovich; G. Romanenko; M. Tkachenko (Bogomolets National Medical University, 2016)
This article shows the possibility of dynamic hepatobiliary scintigraphy to identify and follow-up at postcholecystectomy syndrome. It was found that after cholecystectomy in patients with calculous cholecystitis the function of the liver parenchyma not fully recovered independently. The degree of the final defeat of the hepatobiliary system is directly dependent on the activity of the main flow of the process, its duration, adherence to physician recommendations and following prescribed further medication.